EDUKASI DAN PELATIHAN PRAKTIK KEAMANAN PRODUKSI PANGAN UMKM YANG EFEKTIF - Triyono, Triyono; Suroso, Brian Ahmad; Devara, Hafiz Rama; Susanti, Siti; Sulistianingsih, Dewi (Universitas Mataram, 2025)
This program aims to develop and implement effective education and training on food production safety practices for micro, small, and medium enterprises (MSMEs). The activity was conducted in Karangsari Sub-district, Kendal Regency, as a form of community service through a student community engagement (KKN) program. The training materials focused on food safety standards, hygiene and sanitation, and proper food handling. The main goal was to enhance the health and safety practices of local entrepreneurs by improving food safety standards, preventing contamination, and ensuring compliance with applicable regulations. A evidence-based approach was used to evaluate the effectiveness of the training methods implemented. The evaluation included analysis of success factors, challenges, and participant responses, with local context as a key consideration in assessing the program's relevance. This study contributes to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being), SDG 8 (Decent Work and Economic Growth), and SDG 12 (Responsible Consumption and Production). Through this training, MSMEs gained knowledge and skills to produce safe and high-quality food products. The practical guidelines developed in this program were designed for easy field implementation. As a result, MSMEs are expected to develop their businesses sustainably, safely, and in compliance with standards. This program also strengthens community involvement in supporting a healthy and inclusive local economic development. It successfully increased MSMEs’ knowledge and practices in food safety, supporting both sustainable business development and public health.